2022
DOI: 10.1007/jhep11(2022)164
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of large N glueballs: holography vs lattice

Abstract: Recently there has been a notable progress in the study of glueball states in lattice gauge theories, in particular extrapolating their spectrum to the limit of large number of colors N. In this note we compare the large N lattice results with the holographic predictions, focusing on the Klebanov-Strassler model, which describes a gauge theory with $$ \mathcal{N} $$ N = 1 supersymmetry. We note that glueball spectrum demonstrates approximate universality across a range of gau… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…The graviton field is related to a spin two color-neutral operator in the boundary theory and by the spectral theorem, the two point function of such an operator will have a pole at the mass of the lightest particle state that can be created by such an operator. This was studied by [54] in a recent paper where the author attempted to fit the known glueball spectrum to hardwall AdS computations in five dimensions (a recent review comparing holographic results to lattice can be found in [62]). Using linearized Einstein's equations in thermal AdS, the author fit the computed glueball masses to lattice data which fixed the IR-cutoff z g in physical units.…”
Section: Physical Unitsmentioning
confidence: 99%
“…The graviton field is related to a spin two color-neutral operator in the boundary theory and by the spectral theorem, the two point function of such an operator will have a pole at the mass of the lightest particle state that can be created by such an operator. This was studied by [54] in a recent paper where the author attempted to fit the known glueball spectrum to hardwall AdS computations in five dimensions (a recent review comparing holographic results to lattice can be found in [62]). Using linearized Einstein's equations in thermal AdS, the author fit the computed glueball masses to lattice data which fixed the IR-cutoff z g in physical units.…”
Section: Physical Unitsmentioning
confidence: 99%